The link between vitamin D, chemerin and metabolic profile in overweight and obese children - preliminary results - Krajewska, Maria; Witkowska-Sędek, Ewelina; Rumińska, Małgorzata; Kucharska, Anna M.; Stelmaszczyk-Emmel, Anna; Sobol, Maria; Majcher, Anna; Pyrżak, Beata (Frontiers in Endocrinology, 2023)
Background: Vitamin D affects adipogenesis, oxidative stress, inflammation, secretion of adipocytokines, lipid metabolism and thermogenesis. Some researchers postulate that those effects could be exerted by the influence of vitamin D on chemerin levels. Aim of the study: We aimed to investigate if there is a link between serum 25-hydroksyvitamin D [25(OH)D], chemerin and metabolic profile in overweight and obese children before and after vitamin D supplementation. Material and methods: The prospective study included 65 overweight and obese children aged 9.08-17.5 years and 26 peers as a control. None of the patients in the study group had received vitamin D within the last twelve months before the study. Results: The study group had lower baseline 25(OH)D (p<0.001) and higher chemerin (p<0.001), triglycerides (TG, p<0.001), triglycerides/high density lipoprotein cholesterol (TG/HDL-C, p<0.001), C-reactive protein (CRP, p<0.05), fasting insulin (p<0.001), Homeostasis Model Assessment - Insulin Resistance (HOMA-IR, p<0.001), alanine aminotransferase (ALT, p<0.001) and uric acid (p<0.001) compared to the control group. Baseline vitamin D was related to fasting insulin (R=-0.29, p=0.021), HOMA-IR (R=-0.30, p=0.016), HDL-C (R=0.29, p=0.020) and uric acid (R=-0.28, p=0.037) in the study group. Baseline chemerin was related to insulin at 30’ (R=0.27, p=0.030), 60’ (R=0.27, p=0.033), 90’ (R=0.26, p=0.037) and 120’ (R=0.26, p=0.040) during the oral glucose tolerance test (OGTT) and ALT (R=0.25, p=0.041) in the study group. Correlation between vitamin D and chemerin (R=-0.39, p=0.046) was found only in the control group. After six months of vitamin D supplementation a decrease in CRP (p<0.01), total cholesterol (p<0.05), ALT (p<0.01), glucose at 150’ OGTT (p<0.05) was observed. Moreover, we noticed a tendency for negative association between 25(OH)D and chemerin levels (p=0.085). Multivariable backward linear regression models were build using baseline vitamin D, baseline chemerin and six months chemerin as the dependent variables. Conclusions: Our study confirmed that vitamin D has positive effect on metabolic profile in overweight and obese children. The relationship between vitamin D and chemerin is not clear, nevertheless we have observed a tendency to decrease chemerin concentrations after improving vitamin D status, even without a significant reduction in body fat mass.